2019
DOI: 10.1002/chem.201903764
|View full text |Cite
|
Sign up to set email alerts
|

Do Anionic π Molecules Aggregate in Solution? A Case Study with Multi‐interactive Ligands and Network Formation

Abstract: An anionic π molecule can form an aggregate when a multi‐interactivity is introduced, in sharp contrast to common anionic molecules that are generally difficult to stack on each other. We found that a multi‐interactive ligand, 2,5,8‐tri(4′‐pyridyl)‐1,3,4,6,7,9‐hexaazaphenalenate (TPHAP−) exhibited a large Stokes shift and an intramolecular charge transfer, both of which were sensitive to hydrogen‐bonding media. An anionic potassium salt of TPHAP− in methanol formed various aggregation states depending on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…3-TPHAP – was prepared as a potassium salt, K­(3-TPHAP), from 3-amidinopyridine hydrochloride and potassium tricyanomethanide in moderate yield (9%) using a modified procedure for the synthesis of K­(4-TPHAP) (Scheme ). The molecule displays several interactive sites, including nine nitrogen atoms, which can be involved in H-bond or coordination bond formation, a large aromatic plane capable of π–π interaction, and delocalized negative charge (Figure a) . The basic characterization of 3-TPHAP – is detailed in the Supporting Information, which revealed that its properties closely resemble those of 4-TPHAP – (Figures S4 and S5).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…3-TPHAP – was prepared as a potassium salt, K­(3-TPHAP), from 3-amidinopyridine hydrochloride and potassium tricyanomethanide in moderate yield (9%) using a modified procedure for the synthesis of K­(4-TPHAP) (Scheme ). The molecule displays several interactive sites, including nine nitrogen atoms, which can be involved in H-bond or coordination bond formation, a large aromatic plane capable of π–π interaction, and delocalized negative charge (Figure a) . The basic characterization of 3-TPHAP – is detailed in the Supporting Information, which revealed that its properties closely resemble those of 4-TPHAP – (Figures S4 and S5).…”
Section: Resultsmentioning
confidence: 96%
“…7 The molecule displays several interactive sites, including nine nitrogen atoms, which can be involved in H-bond or coordination bond formation, a large aromatic plane capable of π−π interaction, and delocalized negative charge (Figure 1a). 9 The basic characterization of 3-TPHAP − is detailed in the Supporting Information, which revealed that its properties closely resemble those of 4-TPHAP − (Figures S4 and S5). 10 Attempts to form coordination networks using the K(3-TPHAP) ligand alone proved challenging.…”
Section: ■ Experimental Sectionmentioning
confidence: 93%
“…The UV-Vis spectra exhibited an absorption band at 335 nm (ɛ = 11114 M À 1 cm À 1 ) similar to previously reported results, which were obtained in different solvents and in the presence of different counter cations. [40,41] This band was assigned to an intramolecular charge transfer (ICT) transition from the HAP core to the three peripheral pyridyl groups. In addition, TPHAP compounds were shown to display photoluminescence at 25 °C.…”
Section: Resultsmentioning
confidence: 99%
“…[42][43][44] Due to the intramolecular charge transfer nature of this transition, the excitation energy and extinction coefficient could be modulated by modifying the substituent groups. [40,41,45] The possibility of formation of singlet oxygen ( 1 O 2 ) via the energy transfer pathway was considered. The existence of 1 O 2 was confirmed by photooxidation of 1,5-dihydroxynaphthalene (1,5-DHN), which is typically used as a selective trap (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation